ANALISIS PENGARUH UKURAN PERUSAHAAN, LABA/RUGI PERUSAHAAN, UKURAN KAP, SOLVABILITAS, DAN OPINI AUDIT TERHADAP AUDIT DELAY - Sonia, Novi; Hariani, Lilik Sri; Sari, Ati Retna (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2019)
This study aims to determine and analyze the influence of company size, company profit / loss, KAP size, solvency and audit opinion on audit delay on mining companies listed on the Indonesia Stock Exchange in 2015-2017. Samples were taken using a purposive sampling technique totaling 40 companies. Testing of this study uses a classic assumption test and multiple linear regression analysis. The results of this study indicate that the size of the company profit / loss company, KAP size, solvency, and audit opinion simultaneously affect the audit delay . The size of the company affects the audit delay. Profit / loss affects the audit delay company. KAP size does not affect audit delay. Solvency does not affect audit delay. And audit opinion has no effect on audit delay. The R2 test results state that the variables in this study have a 40.2% influence on audit delay. Other recommended variables that can affect audit delay are profitability, company age, liquidity, and auditor turnover.